Deteksi Dini Tumbuh Kembang Balita di Posyandu - Fredy Akbar K; Idawati Ambo Hamsah; Darmiati Darmiati; Mirnawati Mirnawati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; toddlers are a group of children whose age ranges from 0-5 years. The toddler period is an important period in the process of human development because of development fast. Method; Research design using cross-sectional quantitative research, the number of samples obtained 63 respondents under five from four posyandu in the village of Rumpa. The research was conducted on 1 August - 5 September 2020 in the village of Rumpa, Mapilli sub-district, Polewali Mandar district. Result; development of children in the Posyandu in hamlet 1, 98% normal, 2% doubtful, hamlet 2, 82.5% doubtful, 14.5% normal, hamlet 3, 65% normal, 35% doubtful, hamlet 4, 85% doubtful, 15% normal. Conclusion; The growth and development of toddlers who often do posyandu have normal results, while toddlers who do not or do not do posyandu have abnormal growth and development